ANALISIS KINERJA KEUANGAN SEBELUM DAN SESUDAH AKUISISI PT.BERAU COAL ENERGY TBK TAHUN 2009-2013 - ADI SUROSO, DWI SUSANTI. TITIN RULIANA. (EKONOMIA, 2016)
In research background,entered the era of the global market, competition in the business world increasingly stringent, which requires every company to always develop the corporate strategies in order to survive or even thrive. One way to develop it is the merger of several companies. However in reality not a business combination produces good results for the company.The research objective is to identify and analyze differences in financial performance before and after the PT. Berau Coal Energy Tbk. Basic theory used in this research is financial management.The basic theory used is the financial management to determine the financial condition of a company seen from the financial statements presented by a company on a periodic basis. With the tools of financial ratio analysis of liquidity ratios, solvability ratios and profitability ratios. Based on the analysis and discussion of the conclusions of a study using the liquidity ratio: hypothesis is accepted,            because it is based on the current ratio calculation results showed that after the acquisition in the year 2011-2013 decline. Based on the analysis and discussion of the conclusions of a study using the solvability ratios: hypothesis rejected, because it is based on the calculation on the debt to asset ratio showed that after the acquisition in 2011-2013 there was an increase. Based on the analysis and discussion of the conclusions of a study using the profitability ratios: the hypothesis is accepted, because it is based on calculations on return on equity showed that after the acquisition of 2011-2013 decline.